BLOOMS - Koutsomichalis, Marinos (My University, 2026)
Telematic online improvised performance by Solar Return, THENOISER, Jenny Pickett, and other artists - also featuring Marinos Koutsomichalis and students from Cyprus University of Technology for STWST48x6 MORE LESS, Stadtwerkstatt / Ars Electronica